A lithium-ion battery composite lithium supplement based on chemical reaction and its application

By using compound lithium supplement agents based on compound reactions, including lithium compounds and reducing agents in lithium-ion batteries, the problem of low lithium supplement efficiency of compound lithium sources is solved, and stable solid compounds are generated, which improves the lithium supplement efficiency of the battery and Electrochemical properties.

CN115498176BActive Publication Date: 2025-02-11HUZHOU YONGXING LITHIUM BATTERY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210837106.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2025-02-11
Estimated Expiration
2042-07-15

AI Technical Summary

Technical Problem

The lithium supplementation efficiency of lithium supplementation of compound lithium source is low, and the lithium-containing compounds have a high decomposition potential, which produces oxygen and other by-products, affecting battery life.

Method used

Using compound lithium supplement agents based on the compound reaction, including lithium compounds (such as lithium oxide and lithium fluoride) and reducing agents (such as phosphorus, boron, silicon, etc.), the compound reaction is carried out through the action of electric field and thermal energy to generate Stable solid compounds improve lithium replenishment efficiency.

Benefits of technology

The lithium replenishment efficiency of lithium-ion batteries is improved, and the generated oxylate or fluoride salts are highly stable and do not cause side effects, which improves the electrochemical performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003748972360000022
    Figure BDA0003748972360000022
  • Figure BDA0003748972360000024
    Figure BDA0003748972360000024
  • Figure BDA0003748972360000025
    Figure BDA0003748972360000025
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium-ion batteries, and discloses a composite lithium supplement for lithium-ion batteries based on chemical reactions and its application, wherein the composite lithium supplement comprises a lithium compound and a reducing agent; the lithium compound is at least one of lithium oxide and lithium fluoride; the reducing agent is at least one of phosphorus, boron, silicon, sulfur, arsenic, lithium sulfite and lithium arsenite. The oxygen-containing acid salt or fluoride-containing acid salt generated by the composite lithium supplement in the present invention after chemical reaction is stable solid compounds, which not only have no "side effects", but also can improve the conductivity of the battery; the composite lithium supplement is dispersed and added to the positive electrode slurry to achieve the completion of lithium supplementation in the early formation process, improve the lithium supplementation effect, and ensure that the lithium-ion battery has high electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery composite lithium supplement agent based on chemical combination reaction and application thereof. Background Art

[0002] Lithium-ion batteries are important media for the conversion and storage of electrical energy. They have the advantages of high energy density, long cycle life, and good rate performance. They are widely used in portable electronic products, large-scale energy storage, and various power sources. However, the solid electrolyte interface film (SEI) and other "side reactions" formed during the charging and discharging process will cause the initial capacity loss and subsequent capacity decay of the battery, which will directly lead to a decrease in the Coulomb efficiency of the first cycle, a shortened battery life, and a loss of energy density. In order to compensate for the lithium loss caused by various factors (forming irreversible "dead lithium"), industry insiders have studied a variety of lithium replenishment methods, which can be divided into two categories according to the type of lithium source: metal lithium source and compound lithium source.

[0003] The most direct and effective way to replenish lithium is to use a metal lithium source, which includes lithium sheets and lithium powder. This method of replenishing lithium can theoretically achieve 100% "efficiency" (the percentage of active lithium in the mass of the lithium replenisher), but it is very difficult to achieve in terms of technology, mainly because the activity of metal elements is too high. During the manufacturing process of the battery, it is easy to catch fire, explode, and become inactivated. Metal lithium will become inactivated by reacting with oxygen, nitrogen, and water in the air. Lithium replenishment with a compound lithium source is achieved by providing a large amount of irreversible Li + , to compensate for the loss of active lithium in the cycle. The Chinese invention patent with publication number CN104037418A discloses a lithium-ion battery positive electrode membrane and its preparation and application, using a lithium replenishing material based on lithium oxygen compound, lithium source and alkyl lithium. Adding the lithium replenishing material to the positive electrode can achieve the lithium replenishing effect, but the lithium-containing compound has a high decomposition potential, and produces oxygen and other byproducts during the decomposition process, which affects the battery life. Summary of the invention

[0004] In order to solve the technical problem of low lithium replenishment efficiency of compound lithium sources, the present invention provides a lithium-ion battery composite lithium replenisher based on chemical reaction and its application, which adopts chemical reaction to replenish lithium, and its products are solid compounds with no side effects, with high lithium replenishment efficiency and can improve the electrochemical performance and cycle stability of the battery.

[0005] The specific technical scheme of the present invention is:

[0006] In a first aspect, the present invention provides a composite lithium supplement for lithium-ion batteries based on a chemical reaction, wherein the composite lithium supplement comprises a lithium compound and a reducing agent; the lithium compound is at least one of lithium oxide and lithium fluoride; the reducing agent is at least one of phosphorus, boron, silicon, sulfur, arsenic, lithium sulfite and lithium arsenite.

[0007] The composite lithium supplement agent of the present invention can be electrochemically oxidized under the action of electric field and thermal energy, and has high lithium supplement efficiency. It mainly combines in the following ways:

[0008] For lithium oxide and phosphorus or arsenic, they are combined in the following manner:

[0009] R=P or As;

[0010] For lithium oxide and silicon, they are combined as follows:

[0011]

[0012] For lithium oxide and boron, they are combined as follows:

[0013] For lithium oxide and lithium arsenite, combine as follows:

[0014]

[0015] For lithium oxide and lithium sulfite, combine them in the following manner:

[0016]

[0017] For lithium fluoride and boron, they are combined as follows:

[0018]

[0019] For lithium fluoride and silicon, they are combined as follows:

[0020]

[0021] For lithium fluoride and phosphorus or arsenic, they are combined in the following manner:

[0022] R=P or As.

[0023] If more than two compounds are added, multiple reactions will occur. For example, adding lithium fluoride and boron and phosphorus in a certain proportion will cause two chemical reactions; adding lithium oxide and lithium arsenite, lithium sulfite, and phosphorus in a certain proportion will cause three chemical reactions.

[0024] The oxygen-containing acid salt or fluoride-containing acid salt generated by the lithium supplement in the present invention after chemical reaction is stable solid compound, which not only has no "side effect" but also can improve the conductivity of the battery. In particular, lithium hexafluorophosphate, lithium hexafluoroarsenate and lithium tetrafluoroborate therein are proved to be good lithium salts in lithium-ion battery electrolyte.

[0025] Preferably, the composite lithium supplement agent undergoes a chemical reaction during the lithium supplementation process.

[0026] Preferably, the product of the chemical reaction is an oxygen-containing acid salt or a fluoride-containing acid salt.

[0027] Preferably, the product of the chemical reaction is at least one of lithium borate, lithium phosphate, lithium silicate, lithium arsenate, lithium sulfate, lithium tetrafluoroborate, lithium hexafluorosilicate, lithium hexafluorophosphate, and lithium hexafluoroarsenate.

[0028] Preferably, the preparation method of the composite lithium supplement agent is: mixing a lithium compound and a reducing agent, using ethanol as a medium, sand milling for 3 to 6 hours after slurry mixing, and then spray drying under a nitrogen or argon atmosphere to obtain the composite lithium supplement agent.

[0029] Preferably, the mass ratio of the lithium compound to the reducing agent is 0.2 to 10:1.

[0030] At this mass ratio, a more effective chemical reaction can occur, and the uniform dispersion after sand grinding is also higher, so the composite lithium supplement can achieve a better lithium supplement effect.

[0031] Preferably, the lithium oxide or lithium fluoride is pretreated before preparing the composite lithium supplement.

[0032] The pretreatment of the lithium oxide is as follows: dispersing the conductive carbon powder in n-propanol, adding the lithium oxide, sand grinding for 1 to 2 hours, wherein the mass ratio of the conductive carbon powder, the lithium oxide and the n-propanol is 1:20 to 100:20 to 100, and then filtering and drying to obtain the pretreated lithium oxide;

[0033] The pretreatment of the lithium fluoride is as follows: dispersing the conductive carbon powder into water, adding lithium fluoride, sand grinding for 1 to 2 hours, wherein the mass ratio of the conductive carbon powder, lithium fluoride and water is 1:20 to 100:20 to 100, and then filtering and drying to obtain pretreated lithium fluoride.

[0034] Preferably, the reducing agent is pretreated before preparing the composite lithium supplement; the pretreatment of the reducing agent is: dispersing the conductive carbon powder into n-propanol, adding the reducing agent, and sand grinding for 1 to 2 hours, the mass ratio of the conductive carbon powder, the reducing agent, and the n-propanol is 1:20 to 100:20 to 100, and then filtering and drying to obtain the pretreated reducing agent.

[0035] Conductive carbon has a rich pore structure and a large specific surface area, and can adsorb lithium fluoride, lithium oxide and reducing agent well. The pretreatment step can make the lithium fluoride, lithium oxide and reducing agent particles evenly distributed and have a large specific surface area. While being able to form a uniform dispersion, it has high conductivity, thereby promoting the chemical reaction between lithium fluoride, lithium oxide and reducing agent, and thus having a better lithium supplementation effect.

[0036] In a second aspect, the present invention further provides a use of the above-mentioned composite lithium supplement in a lithium ion battery, wherein the composite lithium supplement is added during the preparation of the positive electrode slurry and coated on a current collector to obtain a positive electrode.

[0037] The composite lithium supplement agent of the present invention has better dispersibility in the positive electrode slurry and can better exert its lithium supplement effect.

[0038] Preferably, the positive electrode slurry comprises a positive electrode material; the added amount of the composite lithium supplement agent is 0.4-1.0% of the weight of the positive electrode material.

[0039] Preferably, the composite lithium supplement agent undergoes a chemical reaction in the lithium-ion battery; the chemical reaction occurs during the formation process or during a heat treatment process after the formation process; the temperature of the heat treatment process is 30 to 95° C. and the time is 1 to 3 hours.

[0040] Compared with the prior art, the beneficial effects of the present invention are:

[0041] (1) The composite lithium supplement can achieve the lithium supplement process through the combined action of electric field and thermal energy, retaining the advantage of high stability of the compound lithium supplement;

[0042] (2) The oxygen-containing salts or fluoride-containing salts generated by the compound lithium supplement after chemical reaction are stable solid compounds. They not only have no "side effects", but also can improve the conductivity of the battery. In particular, lithium hexafluorophosphate, lithium hexafluoroarsenate and lithium tetrafluoroborate have been proven to be good lithium salts in lithium-ion battery electrolytes.

[0043] (3) The composite lithium replenisher is dispersed and added into the positive electrode slurry to complete the lithium replenishment in the early formation process, improve the lithium replenishment effect, and ensure that the lithium-ion battery has high electrochemical performance. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with the embodiments.

[0045] Overall embodiment

[0046] 1. Composite lithium supplement

[0047] The composite lithium supplement includes a lithium compound and a reducing agent, wherein the lithium compound is at least one of lithium oxide and lithium fluoride, and the reducing agent is at least one of phosphorus, boron, silicon, sulfur, arsenic, lithium sulfite and lithium arsenite. The composite lithium supplement undergoes a chemical reaction during the lithium supplement process to generate an oxygen-containing acid salt or a fluoride-containing acid salt, which includes lithium borate, lithium phosphate, lithium silicate, lithium arsenate, lithium sulfate, lithium tetrafluoroborate, lithium hexafluorosilicate, lithium hexafluorophosphate or lithium hexafluoroarsenate.

[0048] Preferably, the preparation method of the composite lithium supplement agent is: mixing a lithium compound and a reducing agent in a mass ratio of 0.1 to 10:1, using ethanol as a medium, sand milling for 3 to 6 hours after slurry mixing, and then spray drying in a nitrogen or argon atmosphere to obtain a composite lithium supplement agent.

[0049] In addition, lithium fluoride, lithium oxide and reducing agent can be pretreated before preparing composite lithium supplement:

[0050] The pretreatment of the lithium oxide is as follows: the conductive carbon powder is dispersed in n-propanol, and then lithium oxide is added, and sand milled for 1 to 2 hours, wherein the mass ratio of the conductive carbon powder, lithium oxide, and n-propanol is 1:20 to 100:20 to 100, and then filtered and dried to obtain pretreated lithium oxide; the pretreatment of the lithium fluoride is as follows: the conductive carbon powder is dispersed in water, and then lithium fluoride is added, and sand milled for 1 to 2 hours, wherein the mass ratio of the conductive carbon powder, lithium fluoride, and water is 1:20 to 100:20 to 100, and then filtered and dried to obtain pretreated lithium fluoride;

[0051] The pretreatment of the reducing agent is as follows: dispersing the conductive carbon powder into n-propanol, adding the reducing agent, and sand grinding for 1 to 2 hours, wherein the mass ratio of the conductive carbon powder, the reducing agent, and the n-propanol is 1:20 to 100:20 to 100, and filtering and drying to obtain the pretreated reducing agent.

[0052] 2. Lithium-ion battery positive electrode: The positive electrode slurry includes positive electrode material, composite lithium supplement agent, conductive agent, binder and solvent. The amount of lithium supplement agent added is 0.4-1.0% of the weight of the positive electrode material. The positive electrode slurry is coated on the current collector to obtain the positive electrode.

[0053] Negative electrode: standard graphite electrode.

[0054] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, negative pressure formation is adopted. During the formation process or after the formation, the temperature is raised to 30-95°C at a rate of 1°C per minute and kept at this temperature for 1-3 hours. The formation is terminated after natural cooling, and the sealing nails are welded.

[0055] Example 1

[0056] 1. Composite lithium supplement

[0057] The composite lithium supplement includes lithium fluoride and phosphorus. Lithium fluoride and phosphorus are mixed in a mass ratio of 16:5, ethanol is used as a medium, the slurry is sand-milled for 5 hours, and then spray-dried in a nitrogen atmosphere to obtain the composite lithium supplement. The composite lithium supplement undergoes a chemical reaction during the lithium supplement process to generate lithium hexafluorophosphate.

[0058] 2. Lithium-ion battery

[0059] Positive electrode: The ternary positive electrode material NCM811, conductive carbon black SP, binder PVDF and solvent NMP with a mass ratio of 95:3:2 are mixed evenly, and then a composite lithium supplement is added to obtain a positive electrode slurry. The added amount of the composite lithium supplement is 0.5% of the weight of the ternary positive electrode material NCM811, and the added amount of the solvent NMP is 60% of the weight of the positive electrode slurry; the positive electrode slurry is coated on an aluminum foil to obtain a positive electrode.

[0060] Negative electrode: standard graphite electrode.

[0061] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, a negative pressure of 0.05MPa is used. After the formation is completed, the temperature is raised to 85°C at a rate of 1°C per minute and kept at this temperature for 1.5 hours. After the temperature drops naturally, the sealing nails are welded.

[0062] Example 2

[0063] 1. Composite lithium supplement

[0064] The composite lithium supplement includes lithium fluoride and boron. Lithium fluoride and boron are mixed in a mass ratio of 3:1, ethanol is used as a medium, the slurry is sand-milled for 5 hours, and then spray-dried in a nitrogen atmosphere to obtain the composite lithium supplement. The composite lithium supplement undergoes a chemical reaction during the lithium supplement process to generate lithium tetrafluoroborate.

[0065] 2. Lithium-ion battery

[0066] Positive electrode: The ternary positive electrode material NCM811, conductive carbon black SP, binder PVDF and solvent NMP with a mass ratio of 95:3:2 are mixed evenly, and then a composite lithium supplement is added to obtain a positive electrode slurry. The added amount of the composite lithium supplement is 0.6% of the weight of the ternary positive electrode material NCM811, and the added amount of the solvent NMP is 60% of the weight of the positive electrode slurry; the positive electrode slurry is coated on an aluminum foil to obtain a positive electrode.

[0067] Negative electrode: standard graphite electrode.

[0068] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, a negative pressure of 0.05MPa is used. After the formation is completed, the temperature is raised to 70°C at a rate of 1°C per minute and kept at this temperature for 2 hours. After the temperature drops naturally, the sealing nails are welded.

[0069] Example 3

[0070] 1. Composite lithium supplement

[0071] The composite lithium supplement includes lithium oxide and phosphorus. Lithium oxide and phosphorus are mixed in a mass ratio of 3:1, ethanol is used as a medium, the slurry is sand-milled for 5 hours, and then spray-dried in a nitrogen atmosphere to obtain the composite lithium supplement. The composite lithium supplement undergoes a chemical reaction during the lithium supplement process to generate lithium phosphate.

[0072] 2. Lithium-ion battery

[0073] Positive electrode: The ternary positive electrode material NCM811, conductive carbon black SP, binder PVDF and solvent NMP with a mass ratio of 95:3:2 are mixed evenly, and then a composite lithium supplement is added to obtain a positive electrode slurry. The added amount of the composite lithium supplement is 0.5% of the weight of the ternary positive electrode material NCM811, and the added amount of the solvent NMP is 60% of the weight of the positive electrode slurry; the positive electrode slurry is coated on an aluminum foil to obtain a positive electrode.

[0074] Negative electrode: standard graphite electrode.

[0075] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, a negative pressure of 0.05MPa is used. After the formation is completed, the temperature is raised to 85°C at a rate of 1°C per minute and kept at this temperature for 1.5 hours. After the temperature drops naturally, the sealing nails are welded.

[0076] Example 4

[0077] 1. Composite lithium supplement

[0078] The composite lithium supplement includes lithium oxide and lithium arsenite. Lithium oxide and lithium arsenite are mixed in a mass ratio of 12:5, ethanol is used as a medium, the slurry is sand-milled for 6 hours, and then spray-dried in a nitrogen atmosphere to obtain the composite lithium supplement. The composite lithium supplement undergoes a chemical reaction during the lithium supplement process to generate lithium phosphate.

[0079] 2. Lithium-ion battery

[0080] Positive electrode: The ternary positive electrode material NCM811, conductive carbon black SP, binder PVDF and solvent NMP with a mass ratio of 95:3:2 are mixed evenly, and then a composite lithium supplement is added to obtain a positive electrode slurry. The added amount of the composite lithium supplement is 0.4% of the weight of the ternary positive electrode material NCM811, and the added amount of the solvent NMP is 60% of the weight of the positive electrode slurry; the positive electrode slurry is coated on an aluminum foil to obtain a positive electrode.

[0081] Negative electrode: standard graphite electrode.

[0082] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, a negative pressure of 0.05MPa is used. After the formation is completed, the temperature is raised to 90°C at a rate of 1°C per minute and kept at this temperature for 2 hours. After the temperature drops naturally, the sealing nails are welded.

[0083] Example 5

[0084] The difference from Example 1 is that lithium fluoride and the reducing agent are pretreated before preparing the composite lithium supplement agent.

[0085] 1. Composite lithium supplement

[0086] The composite lithium supplement includes pre-treatment of lithium fluoride and pre-treatment of phosphorus. The pre-treatment process includes the following steps:

[0087] Disperse 2g of conductive carbon powder into 50g of water, add 100g of lithium fluoride, grind for 2h, filter and dry to obtain pretreated lithium fluoride;

[0088] 2 g of conductive carbon powder was dispersed in 80 g of n-propanol, and then 50 g of red phosphorus powder was added. The mixture was sand-milled for 1 h, and then filtered and dried to obtain the pretreated phosphorus element.

[0089] The pretreated lithium fluoride and the pretreated phosphorus element were mixed at a mass ratio of 16:5, ethanol was used as a medium, the slurry was sand-milled for 5 hours, and then spray-dried in a nitrogen atmosphere to obtain a composite lithium supplement. The composite lithium supplement reacted during the lithium supplement process to generate lithium hexafluorophosphate.

[0090] 2. Lithium-ion battery positive electrode: The ternary positive electrode material NCM811, conductive carbon black SP, binder PVDF and solvent NMP with a mass ratio of 95:3:2 are mixed evenly, and then a composite lithium supplement is added to obtain a positive electrode slurry. The amount of the composite lithium supplement is 0.5% of the weight of the ternary positive electrode material NCM811, and the amount of the solvent NMP is 60% of the weight of the positive electrode slurry. The positive electrode slurry is coated on an aluminum foil to obtain a positive electrode.

[0091] Negative electrode: standard graphite electrode.

[0092] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, a negative pressure of 0.05MPa is used. After the formation is completed, the temperature is raised to 85°C at a rate of 1°C per minute and kept at this temperature for 1.5 hours. After the temperature drops naturally, the sealing nails are welded.

[0093] Example 6

[0094] The difference from Example 1 is that lithium fluoride is pretreated before preparing the composite lithium supplement agent.

[0095] 1. Composite lithium supplement

[0096] The composite lithium supplement includes pre-treatment of lithium fluoride and phosphorus. The pre-treatment process includes the following steps:

[0097] 2 g of conductive carbon powder was dispersed in 50 g of water, and then 100 g of lithium fluoride was added. The mixture was sand-milled for 2 h, and then filtered and dried to obtain pretreated lithium fluoride.

[0098] The pretreated lithium fluoride and phosphorus element were mixed in a mass ratio of 16:5, ethanol was used as a medium, the slurry was sand-milled for 5 hours, and then spray-dried in a nitrogen atmosphere to obtain a composite lithium supplement. The composite lithium supplement reacted during the lithium supplement process to generate lithium hexafluorophosphate.

[0099] 2. Lithium-ion battery positive electrode: The ternary positive electrode material NCM811, conductive carbon black SP, binder PVDF and solvent NMP with a mass ratio of 95:3:2 are mixed evenly, and then a composite lithium supplement is added to obtain a positive electrode slurry. The amount of the composite lithium supplement is 0.5% of the weight of the ternary positive electrode material NCM811, and the amount of the solvent NMP is 60% of the weight of the positive electrode slurry. The positive electrode slurry is coated on an aluminum foil to obtain a positive electrode.

[0100] Negative electrode: standard graphite electrode.

[0101] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, a negative pressure of 0.05MPa is used. After the formation is completed, the temperature is raised to 85°C at a rate of 1°C per minute and kept at this temperature for 1.5 hours. After the temperature drops naturally, the sealing nails are welded.

[0102] Example 7

[0103] The difference from Example 1 is that the reducing agent is pretreated before preparing the composite lithium supplement agent.

[0104] 1. Composite lithium supplement

[0105] The composite lithium supplement includes lithium fluoride and pre-treated phosphorus. The pre-treatment process includes the following steps:

[0106] 2 g of conductive carbon powder was dispersed in 80 g of n-propanol, and then 50 g of red phosphorus powder was added. The mixture was sand-milled for 1 h, and then filtered and dried to obtain the pretreated phosphorus element.

[0107] The lithium fluoride and the pretreated phosphorus element are mixed in a mass ratio of 16:5, ethanol is used as a medium, the slurry is sand-milled for 5 hours, and then spray-dried in a nitrogen atmosphere to obtain a composite lithium supplement. The composite lithium supplement undergoes a chemical reaction during the lithium supplement process to generate lithium hexafluorophosphate.

[0108] 2. Lithium-ion battery positive electrode: The ternary positive electrode material NCM811, conductive carbon black SP, binder PVDF and solvent NMP with a mass ratio of 95:3:2 are mixed evenly, and then a composite lithium supplement is added to obtain a positive electrode slurry. The amount of the composite lithium supplement is 0.5% of the weight of the ternary positive electrode material NCM811, and the amount of the solvent NMP is 60% of the weight of the positive electrode slurry. The positive electrode slurry is coated on an aluminum foil to obtain a positive electrode.

[0109] Negative electrode: standard graphite electrode.

[0110] The positive and negative electrodes are rolled, assembled, and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, a negative pressure of 0.05MPa is used. After the formation is completed, the temperature is raised to 85°C at a rate of 1°C per minute and kept at this temperature for 1.5 hours. After the temperature drops naturally, the sealing nails are welded.

[0111] Comparative Example 1

[0112] The difference from Example 1 is that no composite lithium supplement agent is added.

[0113] Positive electrode: The ternary positive electrode material NCM811, the conductive carbon black SP, the binder PVDF and the solvent NMP in a mass ratio of 95:3:2 were mixed evenly to obtain a positive electrode slurry, and the added amount of the solvent NMP was 60% of the weight of the positive electrode slurry; the positive electrode slurry was coated on an aluminum foil to obtain a positive electrode.

[0114] Negative electrode: standard graphite electrode.

[0115] The positive and negative electrodes are rolled, assembled and injected into a square aluminum shell lithium-ion battery. In the lithium-ion battery formation process, 0.05MPa negative pressure is used. After the formation is completed, the temperature is naturally lowered and the sealing nails are welded.

[0116] Table 1

[0117]

[0118]

[0119] In Table 1, the lithium-ion battery was subjected to charge and discharge cycle tests at a voltage of 2.75 to 4.25 V and a rate of 0.2C.

[0120] As shown in Table 1, as shown in Examples 1-7 and Comparative Example 1, the composite lithium supplement agent of the present invention can achieve a high lithium supplement efficiency, especially lithium hexafluorophosphate, lithium hexafluoroarsenate and lithium tetrafluoroborate generated by the chemical reaction, which are all proven to be good lithium salts in lithium ion battery electrolytes and can improve the conductivity of the battery. In addition, the lithium compound and the reducing agent can further improve the conductivity of the lithium supplement agent after pretreatment, and promote the occurrence of the chemical reaction, thereby improving the composite dispersion effect of the lithium supplement agent, and thus the lithium supplement effect is better.

[0121] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0122] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A lithium-ion battery composite lithium supplement based on chemical reaction, characterized in that: The composite lithium supplement agent comprises a lithium compound and a reducing agent; the lithium compound is lithium oxide, and the reducing agent is lithium sulfite or lithium arsenite; the composite lithium supplement agent undergoes a chemical reaction during the lithium supplement process, and the product of the chemical reaction is lithium sulfate or lithium arsenate; the lithium compound and the reducing agent are pretreated before preparing the composite lithium supplement agent; The pretreatment of lithium oxide is as follows: disperse the conductive carbon powder in n-propanol, add lithium oxide, and sand grind for 1~2 hours. The mass ratio of the conductive carbon powder, lithium oxide, and n-propanol is 1:20~100:20~100, and then filter and dry. The pretreatment of the reducing agent is as follows: disperse the conductive carbon powder in n-propanol, add the reducing agent, and sand grind for 1~2 hours. The mass ratio of the conductive carbon powder, reducing agent, and n-propanol is 1:20~100:20~100, and then filter and dry.

2. The lithium-ion battery composite lithium supplement based on chemical reaction according to claim 1, characterized in that: The preparation method of the composite lithium supplement agent is as follows: a lithium compound and a reducing agent are mixed, ethanol is used as a medium, the slurry is mixed and sand milled for 3 to 6 hours, and then spray-dried in a nitrogen or argon atmosphere to obtain the composite lithium supplement agent.

3. The lithium-ion battery composite lithium supplement agent based on chemical reaction according to claim 1 or 2, characterized in that: The mass ratio of the lithium compound to the reducing agent is 0.2-10:

1.

4. The lithium-ion battery composite lithium supplement based on chemical reaction according to claim 1, characterized in that: The mass ratio of lithium oxide to lithium arsenite is 12:

5.

5. The use of the composite lithium supplement agent in a lithium ion battery according to any one of claims 1 to 4, characterized in that: The composite lithium supplement is added during the preparation of the positive electrode slurry, and is coated on the current collector to obtain the positive electrode.

6. The use according to claim 5, characterized in that The positive electrode slurry includes a positive electrode material; the added amount of the composite lithium supplement is 0.4-1.0% of the weight of the positive electrode material.

7. The use according to claim 6, characterized in that The added amount of the composite lithium supplement is 0.4% of the weight of the positive electrode material.

8. The use according to claim 6, characterized in that The added amount of the composite lithium supplement is 0.5% of the weight of the positive electrode material.

9. The use according to claim 5 or 6, characterized in that: The composite lithium supplement agent undergoes a chemical reaction in the lithium ion battery; the chemical reaction occurs during the formation process or during a heat treatment process after the formation process; the temperature of the heat treatment process is 30-95° C. and the time is 1-3 hours.

Citation Information

Patent Citations

  • Lithium ion battery anode film, preparation and application thereof

    CN104037418A

  • Lithium ion battery positive electrode sheet, preparation method of lithium ion battery positive electrode sheet, and lithium ion battery

    CN106384808A

  • Preparation method of lithium supplementing conductive slurry, lithium supplementing conductive paste, lithium ion battery and electronic equipment

    CN112447963A

  • Lithium supplement material, positive electrode material and lithium ion secondary battery

    CN113921801A

  • Cathode additives for lithium-ion batteries

    US20160365566A1